Infrared laser photobiomodulation (lambda 830 nm) on bone tissue around dental implants: A Raman spectroscopy and scanning electronic microscopy study in rabbits - Lopes, Cibelle B.; Pinheiro, Antonio L. B.; Sathaiah, Sokki; Da Silva, Newton Soares; Salgado, Miguel A. C. (Mary Ann Liebert, Inc., 2007)
Objective: the aim of this study was to assess, through Raman spectroscopy, the incorporation of calcium hydroxyapatite (CHA; similar to 960 cm(-1)), and scanning electron microscopy (SEM), the bone quality on the healing bone around dental implants after laser photobiomodulation ( lambda 830 nm). Background Data: Laser photobiomodulation has been successfully used to improve bone quality around dental implants, allowing early wearing of prostheses. Methods: Fourteen rabbits received a titanium implant on the tibia; eight of them were irradiated with lambda 830 nm laser ( seven sessions at 48-h intervals, 21.5 J/cm(2) per point, 10 mW, phi similar to 0.0028 cm(2), 86 J per session), and six acted as control. The animals were sacrificed 15, 30, and 45 days after surgery. Specimens were routinely prepared for Raman spectroscopy and SEM. Eight readings were taken on the bone around the implant. Results: the results showed significant differences on the concentration of CHA on irradiated and control specimens at both 30 and 45 days after surgery ( p < 0.001). Conclusion: It is concluded that infrared laser photobiomodulation does improve bone healing, and this may be safely assessed by Raman spectroscopy or SEM.